"A Home in My Body": Migration, Infection, and Privilege in Porochista Khakpour's Sick. (30th June 2022) - Green, Chloe R.
Abstract: This essay explores the connection between physical and geopolitical boundaries in Porochista Khakpour's 2018 memoir Sick in the forms of immigration, national identity, and cross-country migration, and the bodily boundaries that protect against infection. Rather than equating the body politic with the immune system, the author argues that Sick 's nonlinear structure creates an ideal form for representing an illness that is primarily characterized by uncertainty and multiplicity. The author then discusses how Khakpour's connection of different states of privilege—namely, relating to class, race, and diagnosis—to this uncertain state of existence creates a form of life writing that resists the Western-centrism of narratives of illness and migration alike.